(untitled) (African Journal of Biomedical Research, 2022)
The objective of this work was to evaluate the hypoglycaemic and hypolipidemic effect of alcoholic extract of common sage (Salvia officinalis) on streptozotocin-induced diabetic rabbits. Twenty five male rabbits of weight 950g- 1150g were used for the study. The animals were grouped into 5 of 5 rabbits each. Group A- Diabetic control, Group B - Diabetic rabbits treated with glibenclamide (0.25 mg/kg), Group C - Diabetic rabbits treated with alcoholic leaf extract at 250 mg/kg and Group D - Diabetic rabbits treated with the leaf extract at 500 mg/kg. Group E- served as normal non-diabetic control. The animals were given a standard diet and water ad libitum. Diabetes was induced in the rabbits by a single intra-peritoneal injection of freshly prepared streptozotocin 50 mg/kg b.w. followed by 120 mg/kg of nicotinamide in 0.1 M citrate buffer, pH 4.5 in a volume of 0.5 ml/kg b.w. Blood samples were collected on the 1st, 7th, 14th and 21st days from the marginal ear vein of the animals and analysed for blood glucose and lipid profile levels. The standard/investigational drugs treated rabbits showed a marked decrease in the level of blood glucose when compared with the diabetic control at a significant level of p < 0.001. The alcoholic extract of common sage leaf (at 250mg/dl) showed a significant decrease (p < 0.05) compared with the diabetic control rabbits. Equally, the leaf extract (at 500mg/dl) showed a significant decrease (p < 0.001) in the blood glucose levels when compared with the diabetic control group. The administration of the leaf extract at 250mg/dl and 500mg/dl to the animals prevented gross alterations in the lipid profile levels. The alcoholic leaf extract of common sage (Salvia officinalis) also has hypoglycaemic and hypolipidemic activity on streptozotocin -induced diabetic rabbits.